Characterization of Aggregatibacter actinomycetemcomitans in Chronic Oral Inflammatory Conditions Using Molecular Techniques in Eastern India (Bangladesh Journal of Medical Science, 2026)
Background Chronic oral inflammatory diseases such as periodontitis are considered major causes of tooth loss. Among periodontal pathogens, Aggregatibacter actinomycetemcomitans is a major pathogen associated with aggressive and chronic forms of periodontal diseases. Molecular diagnostic methods have greatly contributed to the detection and characterization of this pathogen and its virulence factors. Aim To characterize Aggregatibacter actinomycetemcomitans in chronic oral inflammatory conditions using molecular techniques in an Eastern Indian population. Materials and Methods A cross-sectional study was performed among 120 participants suffering from chronic periodontitis, gingivitis, and oral potentially malignant disorders. Plaque samples were obtained from the subgingival region, and genomic DNA was isolated. Species-specific PCR was performed for detecting A. actinomycetemcomitans using the 16S rRNA gene. Multiplex PCR was performed for detecting virulence genes such as leukotoxin (ltxA) and cytolethal distending toxin (cdtB). Clinical periodontal parameters were associated with the study. Results A. actinomycetemcomitans was found in 63.3% of chronic periodontitis cases, 34.4% of gingivitis cases, and 21.7% of OPMD cases. The virulence gene study showed that 58% of cases were ltxA positive, and 46% were cdtB positive. The presence of virulence genes had significant correlation with probing depth and clinical attachment loss. Conclusion PCR-based molecular detection provides highly sensitive identification of A. actinomycetemcomitans. The findings emphasize the importance of virulence gene profiling in understanding periodontal disease progression in Eastern Indian populations.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S229-S235